«Il consumatore di sé»: the ‘geographical’ map for designing new marketing and communication paths - Pornaro, Fabio (Community Notebook. People, Education and Welfare in the Society 5.0, 2024)
With «Il consumatore narratore di sé» Risso wants to represent an accurate ‘geographical’ map of contemporary consumption and consumers, in which what we might call the territories within which consumers themselves act in search of a construction of the self are just as accurately described.